Macroinvertebrate Distribution In Relation To Water Quality In The Middle Reach Of Kerian River Basin - Abdul, Nurul Huda (2012)
Aquatic macroinvertebrates collected from May 2008 to August 2009 from three rivers; Bogak, Serdang and Kerian in middle reach of Kerian River Basin (KRB) were represented by 120 genera of which 8194 individuals from 59 families and 13 orders. Their abundances varied significantly among sampling occasions (F(8,261) = 2.132, p < 0.05) in different rivers (F(2,267) = 22.743, p < 0.05). Majority of the macroinvertebrates were tolerant predators and collector-filterers. Different riparian vegetations, macrophytes‟ growth, substrates types and seasonal changes were important factors regulating habitat suitability for the macroinvertebrates in this part of KRB. Except for turbidity and TSS, nine water parameters were significantly different among rivers (Kruskal-Wallis test, p < 0.05). Pleidae as well as Gomphidae, Palaemonidae and Chlorocyphidae were very sensitive to changes in the aquatic habitats. Water velocity strongly influenced hemipteran‟s (mainly Pleidae) distribution (ρ = -0.565, p < 0.05). Abundance of Gomphidae was negatively influenced by increasing amount of Zn (ρ = -0.557) in river sediment. The Water Quality Index (WQI) categorized quality of the three rivers as “clean” and “moderately clean” (Classes II – III). Moreover, the scores of biological indices; Family Biotic Index (FBI), Biological Monitoring Working Party (BMWP) and Average Score Per Taxon (ASPT), also implied that the water quality was “clean” to “moderately clean”. In Serdang River, dragonfly assemblage could be used as surrogate taxa for water quality monitoring. Out of 5655 individuals (from 8 families and 28 taxa), Pseudagrion spp. was the most abundant (41.22%) followed by Onychothemis sp. (17.12%). Habitat preference of some genera was clearly observed and Odonate community in completely shaded area with vegetation canopy was different from that of unshaded area (Beta diversity = 0.688). However, there are similarities of genera shared between partly shaded and unshaded areas. River physical characteristics, types of pollutants discharge as well as seasonal factor influenced odonate assemblages thus led to shift in odonates dominant in Serdang River.